Tellurite-Mediated Damage to the Escherichia Coli Ndh-Dehydrogenases and Terminal Oxidases in Aerobic Conditions - Vasquez-Guzman, C; Arenas-Salinas, F; Cornejo-Leiva, F; Díaz-Vásquez, W; Abarca-Lagunas, M (Academic Press, 2015)
Escherichia coli exposed to tellurite shows augmented membrane lipid peroxidation and ROS content. Also, reduced thiols, protein carbonylation, [Fe-S] center dismantling, and accumulation of key metabolites occur in these bacteria. In spite of this, not much is known about tellurite effects on the E. coli electron transport chain (ETC). In this work, tellurite-mediated damage to the E. coli ETC s NADH dehydrogenases and terminal oxidases was assessed. Mutant lacking ETC components showed delayed growth, decreased oxygen consumption and increased ROS in the presence of the toxicant. Membranes from tellurite-exposed E. coli exhibited decreased oxygen consumption and dNADH/NADH dehydrogenase activity, showing an impairment of NDH-I but not of NDH-II activity. Regarding terminal oxidases, only the bo oxidase complex was affected by tellurite. When assaying NDH-I and NDH-II activity in the presence of superoxide, the NDH-I complex was preferentially damaged. The activity was partly restored in the presence of reducing agents, sulfide and Fe2+ under anaerobic conditions, suggesting that damage affects NDH-I [4Fe-4S] centers. Finally, augmented membrane protein oxidation along with reduced oxidase activity was observed in the presence of the toxicant. Also, the increased expression of genes encoding alternative terminal oxidases probably reflects a cell s change towards anaerobic respiration when facing tellurite. © 2014 Elsevier Inc. All rights reserved.